Flexural capacity of concrete beams reinforced with steel and fibre‐reinforced polymer (FRP) bars - Leung, Hau Yan (Journal of Civil Engineering and Management, 2004)
Although much research on concrete beams reinforced with fibre‐reinforced polymer (FRP) rods has been conducted in recent years, their use still does not receive the attention it deserves from practicising engineers. This is attributed to the fact that FRP is brittle in nature and the collapse of FRP‐reinforced concrete member may be catastrophic. A rational beam design can incorporate a hybrid use of FRP rods and steel rods. Current design codes only deal with steel‐reinforced or FRP‐reinforced concrete members. Therefore in this study some design charts and equations for concrete beam sections reinforced with FRP rods and steel rebars were generated. Results from the theoretical derivations agreed well with experimental data. First Published Online: 14 Oct 2010